2020
DOI: 10.1590/1982-7849rac2020190390
|View full text |Cite
|
Sign up to set email alerts
|

Palmas para o E-Dinheiro! A Evolução Digital de uma Moeda Social Local

Abstract: RESUMO Este caso de ensino aborda a digitalização da moeda social local Palmas, emitida desde o início dos anos 2000 em papel-moeda pelo Banco Palmas, para um novo modelo híbrido de mobile payments e mobile money, denominado E-Dinheiro. Trata-se de um empreendimento de desenvolvimento social e de inclusão financeira com amplo reconhecimento nacional e internacional. Ao contar a história do banco comunitário e algumas de suas iniciativas, pretende-se demonstrar o processo de inovação em uma fintech soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…It should be noted that the contribution to cope with eligibility problems stems from proximity to the target audience (Gonzalez, Diniz, & Pozzebon, 2015). Such proximity, intrinsic to the social technology of community banks, is strengthened by the use of DCC, as previously highlighted in the speech by Joaquim Mello (Cernev & Diniz, 2020). In addition, the digital payment system of DCCs contributes to logistics (Bader & Savoya, 2013), and the mechanism of territorial action of DCCs contributes to local development.…”
Section: Emergency Basic Income and The Case Of Mumbuca E-dinheiromentioning
confidence: 96%
See 2 more Smart Citations
“…It should be noted that the contribution to cope with eligibility problems stems from proximity to the target audience (Gonzalez, Diniz, & Pozzebon, 2015). Such proximity, intrinsic to the social technology of community banks, is strengthened by the use of DCC, as previously highlighted in the speech by Joaquim Mello (Cernev & Diniz, 2020). In addition, the digital payment system of DCCs contributes to logistics (Bader & Savoya, 2013), and the mechanism of territorial action of DCCs contributes to local development.…”
Section: Emergency Basic Income and The Case Of Mumbuca E-dinheiromentioning
confidence: 96%
“…More than just a digitalization of local CCs, E-Dinheiro is seen by leaders of community development banks (CDB) as a social technology to promote the solidarity economy, since it enables the creation of new CDBs and complementary currencies using a local microcomputer (Cernev & Diniz, 2020). Conceptually, E-Dinheiro is a hybrid model of mobile money and mobile payments (Cernev & Diniz, 2020) currently being adopted by 48 community development banks, including Banco Mumbuca, whose DCC Mumbuca will be presented below.…”
Section: Complementary Currencies In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest challenges observed in the literature regarding the use and financial and operational viability of local currencies concerns the costs involved in the process of implementation and continuity of projects. Empirical research carried out, for example, by Seyfang and Longhurst ( 2016 ), Majuri ( 2019 ) and Cernev and Diniz ( 2020 ) on the subject of social currencies has shown that a potential rupture, both operational and in terms of amplification, is related to the advancement of technology and the insertion of mechanisms for the use of digital currencies that allow extensive access and propagation of the currency, a reduction in printing costs and the maintenance of more complex formal structures; this aspect can make social currencies viable, which were previously prohibitive, due to the high investment required (Sobiecki 2018 ; Majuri 2019 ; Lim and Nakazato 2019 ). Cernev and Diniz ( 2020 ) add that software development, as well as the adoption and use of mobile payments can also pose difficulties.…”
Section: Social Currenciesmentioning
confidence: 99%
“…A second measure would be to replicate E-Dinheiro to more locations, something that is technologically feasible since a microcomputer enabled in the location is sufficient to operate such a service (Cernev & Diniz, 2020). With the support of the existing CDB methodology and associated with the E-Dinheiro technology, the replication processes would be streamlined.…”
Section: Articulation With the Technological And Payments Ecosystemmentioning
confidence: 99%